A Spectrally Resolved Imaging Method for Investigating Alcohol Pool Fires. Issue 2 (1st February 2016) - Chuah, Keng Hoo; Saito, Kozo; Hashiba, Yu; Gotoda, Hiroshi; Williams, Forman A.
ABSTRACT: An optical method, employing a modified mid-infrared (IR) camera sensitive to alcohol-vapor C–O bond-stretch bands, is introduced for investigating the structures of alcohol fires. Photographs of pool fires, made with the camera, show different information than ordinary visible photographs. Placing a slit and a lens system with a grating between the camera and the fire provides an emission spectrum, which varies continuously with distance along the slit. Measurements with a vertically oriented slit were made at heights up to 10cm above small methanol and ethanol pool fires. The intensities of the alcohol band emissions were found to decrease sharply with increasing height, while those of H2 O and CO2 band emissions gradually increased with height. The sharp alcohol-emission decrease suggests that fuel pyrolysis occurs with increasing height on the fuel side of the stoichiometric surface more rapidly than we thought. Vertical profiles of the average fuel concentrations were estimated from analysis of the data.